An Assessment of the Impact of Laser-Assisted Precision Land Levelling Technology as a Component of Climate-Smart Agriculture in the State of Haryana, India - Gill G (2014)
This assessment covers a component of CIMMYT’s Climate Change-relevant research activities that had their origins prior to 2011, but to which a CC dimension has been added by CCAFS interventions. It focuses on Laser-Assisted Precision Land Levelling (LLL) in the western Indo-Gangetic Plain. This technology which was first introduced into the region in 2011 under the auspices of the Rice-Wheat Consortium for the Indo-Gangetic Plains, an initiative that was convened jointly by CIMMYT, the International Rice Research Institute and a number of national and sub-national research institutes in the region.